Zombie Companies in the Corona Pandemic or the phenomenon of covertly over-indebted companies in Germany - Marco Becker (ZBW - Leibniz Information Centre for Economics, 2021)
The phenomenon of covertly over-indebted companies – also known colloquially as zombie companies – is not new. They occur more frequently in times of crisis, including during the current Corona pandemic. In addition to covertly over-indebtedness, there is now the added factor of latent insolvency. This article will take a closer look at the emergence of zombie companies in Germany during the Corona pandemic. – – Das Phänomen verdeckt überschuldeter Unternehmen – umgangssprachlich auch als »Zombie-Unternehmen« bekannt – ist nicht neu. Sie treten vermehrt in Krisenzeiten auf, so auch während der aktuellen Corona-Pandemie. Neben der verdeckten Überschuldung kommt jetzt noch der Faktor der latenten Zahlungsunfähigkeit hinzu. In diesem Artikel soll die Entstehung der »Zombie-Unternehmen« in Deutschland während der Corona-Pandemie näher untersucht werden.
Keywords: 330; zombie companies; covertly over-indebted companies